EFEKTIVITAS PERAN RW DALAM PENYALURAN ASPIRASI DAN PEMBANGUNAN DI KELURAHAN SARAGI BUTON - Irman Irman; La Aris; Nastia Nastia (Jurnal Multidisipliner Bharasumba, 2026)
Rukun Warga (RW) is a community institution that has a strategic role in channeling community aspirations and supporting development at the village level. However, the effectiveness of RW's position in local government practice still shows variation between regions. This study aims to analyze the effectiveness of RW's position in channeling community aspirations and supporting development in Saragi Village, Pasarwajo District, Buton Regency. This study uses a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation, with informants consisting of village officials, RW administrators, and community leaders. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the effectiveness of RW is determined by the ability to capture and document community aspirations, coordination with the village government, and its impact on community participation in development activities. This study concludes that strengthening the institutional capacity and leadership of RW is a key factor in increasing the effectiveness of distributing aspirations and village development based on community participation.